Behavior Analysis of Intention to Use the Tiomaz Application in E-Ticketing Booking - Tanjung, Rizka Azriani; Harahap, M. Ikhsan; Aisyah, Siti (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2024)
Following the footsteps of the aviation and railway industries that have already switched to digital, land transportation modes such as buses and travel are increasingly adopting e-ticketing systems. One way used by ticket providers is by offering transportation tickets to help travelers buy bus tickets. The purpose of this study was to determine whether TAM can be applied to the use of the Tiomaz application in e-ticketing by evaluating the influence of perceived usefulness (PU) and perceived ease of use (PEOU) on behavior. The population in this study was 10,000 people, namely the number of users who downloaded the Tiomaz application on the Playstore. Meanwhile, the sampling technique used the Slovin formula, namely with a sample size of 99 people. This study used a questionnaire research instrument created based on a literature review. The questionnaire was compiled in several stages, namely 1) Referring to the operational data of previously determined variables; 2 The questionnaire consists of four parts: respondent data, perceived ease of use, perceived efficacy, and behavioral intention; and 3) This study uses a Likert scale from 1 to 5 with the following answers: strongly disagree, disagree, neutral, agree, and strongly agree. Data analysis was conducted using the SPSS application and multiple regression analysis method. The findings of the study indicate that the variable Perceived Ease of Use (X1) has a positive and significant impact on Behavioral Intention (Y), meaning that the easier it is for users to use the application, the greater their desire to use it. In addition, the variable Perceived Usefulness (X2) has a positive and significant impact on Behavioral Intention (Y). Further research is needed to examine other components that may affect user experience.